Preparation and Characterization of Pt Based Mono and Bimetallic Nano Catalysis and Their Application of Citral Hydrogenation - Ananthan, S.A.; Narayanan, V.; Suresh, R.; Giribabu, K. (Asian Journal of Chemistry, 2012)
Carbon nanotubes supported Pt, Ru and Pt-Ru catalysts were prepared by impregnation method and reduced at two different temperatures, 375 ºC (LTR) and 675°C (HTR). The catalysts were characterized by BET surface area measurement, TPD, HR-SEM, EDAX, HR-TEM, XRD and XPS. It was found that the XRD of Pt showed fcc crystalline structure and Ru showed hcp crystalline structures, which is uniformly dispersed with an average particles size of 3.5 nm and zero valence metallic state. The removal of acidic oxygen surface group is observed when heat-treatments in an inert atmosphere at 675 ºC were performed. The bimetallic catalyst of Pt- Ru/MWCNT was found to afford remarkably high conversion levels (88 %) and high selectivity (90 %) provided that a thermal pre-treatment was performed on the catalyst. These results can be rationalized in terms of electron transfer from the support to the metal. The catalysts are environment friendly and can be recycled for more than eight times.